UPAYA DIPLOMASI PEMERINTAH INDONESIA UNTUK MENINGKATKAN JUMLAH WISATAWAN MANCANEGARA PASCA BOM BALI TAHUN 2002 - Elizabeth, Jeane (Global and Policy Journal of International Relations, 2015)
ABSTRACTThe tourism sector still remains one of the major mainstay in the country earn foreign countries. Indonesia is an archipelagic country has its own charm to compete in international tourism. The arrival of foreign tourists to Indonesia, can not be separated because of the charm of Bali which has many wonderful panorama. The development of tourist arrivals to Bali to experience fluctuations due by the bombing in 2002 and 2005. From the Bali bombings in 2002 and 2005, the Indonesian government made diplomatic efforts to increase the number of tourists mancaegara in Bali. The government made a series of diplomatic efforts in the form of international communication using diplomatic measures that track diplomacy first and second track diplomacy. Further efforts Indonesian tourism promotion strategies abroad that use inbound and outbound campaign. Imaging effort after the Bali bombings using positive image that includes socialization activities and role of the media. With all three of these efforts, the image of Bali tourism can be recovered and the number of foreign tourists could increase.Keywords : Indonesian Government Diplomacy Efforts, Tourism, Increased Number of Foreign Tourists, BaliDOI:https://doi.org/10.33005/jgp.v3i01.1962